RETRACTED ARTICLE: Association of the polymorphisms in FOXO1 gene and diabetic nephropathy risk - Jianxia Ma; Yongbin Pei; Peng Xue; Yan Wang; Xiaoxue Bao; Yukun Li (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Jianxia Ma, Yongbin Pei, Peng Xue, Yan Wang, Xiaoxue Bao & Yukun Li (2019) Association of the polymorphisms in FOXO1 gene and diabetic nephropathy risk. Artificial Cells, Nanomedicine, and Biotechnology, 47:1, 1471-1475, DOI: 10.1080/21691401.2019.1601103It has come to our attention that the full authorship list and affiliations for this manuscript, including the study site and ethics committee, were changed after the article was submitted. We have contacted the authors for an explanation, but we have not received a response within the requested timeframe. As determining authorship and the location of where the research was conducted is core to the integrity of published work, we are therefore retracting the article. The authors listed in this publication have been sent notification.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.